2019
DOI: 10.1111/jocd.13054
|View full text |Cite
|
Sign up to set email alerts
|

Novel shampoo reduces hair shedding by contracting the arrector pili muscle via the trace amine‐associated receptor

Abstract: Background Approximately 40% of women experience excessive hair shedding when washing their hair. Previously, we have demonstrated that a topically applied α1 adrenergic receptor agonist can be used to contract the arrector pili muscle of the follicular unit (ie, produce “goose bumps”), increasing the force required to pluck hair by as much as 400%. Subsequently, we reported a topical cosmetic solution containing an α1 adrenergic receptor agonist that reduced hair shedding during brushing by a maximum of 77%. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…This enabled us to define the fundamental 3D structure of vellus hair muscle. Since hair muscle is important for skin regeneration and cosmetics, 29 our results are expected to be helpful for the development of clinical and esthetic treatments…”
Section: Discussionmentioning
confidence: 99%
“…This enabled us to define the fundamental 3D structure of vellus hair muscle. Since hair muscle is important for skin regeneration and cosmetics, 29 our results are expected to be helpful for the development of clinical and esthetic treatments…”
Section: Discussionmentioning
confidence: 99%
“…Recently, their potential role in hair follicle growth and pigmentation has garnered attention. Kovacevic et al (2019) formulated a novel shampoo containing tyramine, which reduced hair shedding in women by contracting the arrector pili muscle through the trace amine-associated receptor. Liu et al (2002) reported that injecting additional spermidine into Merino lamb skin stimulated cell proliferation in the wool bulb and led to fiber growth.…”
Section: Discussionmentioning
confidence: 99%
“…Most intriguingly and in contrast to experiments performed with overexpressed TAAR1 in cell systems as HEK cells, 3-T1AM mediates effects on TAAR1/TAAR2 at nanomolar concentrations in vivo [25]. Of note, TAAR expression (yet unknown subtype) in smooth muscle (part of connecting hair follicles in the scalp to the inner epidermis) and activation by trace amines, such as TYR in shampoo, was recently suspected to reduce hair shedding after washing [26].…”
Section: Trace Amine-associated Receptors As 3-t1am Targetsmentioning
confidence: 98%